Administration of Cabergoline Contributes to Preserving Fertility in Young Hyperprolactinemic Patients With Endometrial Cancer Treated With Medroxyprogesterone Acetate. Issue 3 (1st March 2018) - Erdenebaatar, Chimeddulam; Yamaguchi, Munekage; Saito, Fumitaka; Monsur, Mahina; Honda, Ritsuo; Tashiro, Hironori; Ohba, Takashi; Katabuchi, Hidetaka
Abstract : Background: An association between high levels of serum prolactin and endometrial cancer (EC) has been reported. However, the effect of antiprolactin drugs on hyperprolactinemic patients with EC has not been determined. The aim of this study was to confirm the effect of cabergoline on young hyperprolactinemic patients treated with medroxyprogesterone acetate (MPA) for the preservation of fertility. Methods: A retrospective observational study was conducted to identify patients with atypical endometrial hyperplasia or early-stage EC aged 40 years or younger who were treated with oral MPA in Kumamoto University Hospital between 1998 and 2016. Results: Thirty-four patients were identified and divided into two groups of 17 patients each, including a nonadministration of cabergoline group (noncabergoline group) and an administration of cabergoline group (cabergoline group). The ratio of pathological diagnoses of EC in the noncabergoline group was significantly lower than that in the cabergoline group (29.4% vs 70.6%, P = 0.016). The mean serum prolactin levels showed a significant decrease after the administration of cabergoline in the cabergoline group (25.2 [24.0] vs 5.2 [4.2] ng/mL, P = 0.003), and this decreased level was also significantly lower than that in the noncabergoline group (5.2 [4.2] vs 12.0 [5.0] ng/mL, P < 0.001). Kaplan-Meier analysis conducted for 150 months revealed that the estimated mean period until hysterectomy in the noncabergoline group was significantly shorter than that in the cabergoline group (83.5 vs 140.8 months, P = 0.007). Significant differences were observed in EC but not atypical endometrial hyperplasia based on histological classification (25.6 vs 138.0 months, P = 0.001). Conclusions: The administration of cabergoline may contribute to preserving fertility in young hyperprolactinemic patients with EC who were treated with MPA.